Outward FDI and Domestic Investment - Dierk Herzer; Mechthild Schrooten (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This paper examines the impact of outward foreign direct investment (OFDI) on domestic investment by applying co-integration techniques to macroeconomic time series data for the United Sates and Germany. We show that the two countries differ: In the case of the US, OFDI has positive long-run effects on domestic investment while in the case of Germany the reverse effect is reported.
Keywords: F41; E22; F21; 330; Foreign Direct Investment; Investment; Open Economy Macroeconomics; Direktinvestition; Investition; Offene Volkswirtschaft; Vergleich; Deutschland; USA